2011
DOI: 10.1002/acr.20365
|View full text |Cite
|
Sign up to set email alerts
|

Macrophage activation and coronary atherosclerosis in systemic lupus erythematosus and rheumatoid arthritis

Abstract: Objective. Activation of macrophages may contribute to increased atherosclerosis and coronary artery disease in systemic lupus erythematosus (SLE) and rheumatoid arthritis (RA). Neopterin, a pteridine derivative, is a novel marker of monocyte and macrophage activation that is associated with atherosclerosis and cardiovascular risk in the general population. We examined the hypothesis that macrophage activation is associated with accelerated atherosclerosis in SLE and RA. Methods. We compared serum neopterin co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
41
0
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 48 publications
(44 citation statements)
references
References 39 publications
1
41
0
2
Order By: Relevance
“…This indicates that CVD in rheumatoid arthritis is associated with enhanced mononuclear-(neopterin, CCL2) and B-cell activation (CXCL13), and as a consequence increased immune activity. Rho et al found higher neopterin concentrations in RA and systemic lupus erythematosus compared to healthy controls associated with erythrocyte sedimentation rate but not associated with coronary atherosclerosis in either disease (24). Patients with CVD show elevated levels of several inflammatory mediators -in particular elevated neopterin concentrations have been reported in patients with various cardiovascular diseases like coronary disease, reviewed by Fuchs et al (13), coronary and peripheral artery disease (12).…”
Section: Resultsmentioning
confidence: 99%
“…This indicates that CVD in rheumatoid arthritis is associated with enhanced mononuclear-(neopterin, CCL2) and B-cell activation (CXCL13), and as a consequence increased immune activity. Rho et al found higher neopterin concentrations in RA and systemic lupus erythematosus compared to healthy controls associated with erythrocyte sedimentation rate but not associated with coronary atherosclerosis in either disease (24). Patients with CVD show elevated levels of several inflammatory mediators -in particular elevated neopterin concentrations have been reported in patients with various cardiovascular diseases like coronary disease, reviewed by Fuchs et al (13), coronary and peripheral artery disease (12).…”
Section: Resultsmentioning
confidence: 99%
“…16–19 Serum concentrations of TNFα and IL-6 were measured by multiplex ELISA (Millipore) in study participants (117 SLE, 164 RA and 172 controls).…”
Section: Methodsmentioning
confidence: 99%
“…Monocyte activation is globally higher in SLE, but monocyte activation does not correlate with increased coronary atherosclerosis 15 (Figure 1). …”
Section: Pathogenesis Of Atherosclerosis In Slementioning
confidence: 99%